meso-[5,10,15,20-Tetrakis(4-cyanophenyl)porphyrinato]zinc - Dong, Shuai (International Union of Crystallography, 2011)
In the title compound, [Zn(C(48)H(24)N(8))], the coordination environment of the Zn(2+) ion (site symmetry [Image: see text]) is octahedral, with four indole N atoms forming the equatorial plane and the axial positions being occupied by N atoms from the cyanide groups of neighbouring molecules. In the crystal, adjacent molecules are assembled into a two-dimensional supramolecular framework parallel to ([Image: see text]01) via the coodination bonding. Topology analysis reveals this compound to be a (4,4)-connected network.